Specificities of antibodies to Plasmodium falciparum merozoite surface protein (MSP)-1 19 (2002)
In a survey of children living in South Western Nigeria, plasma levels of anti-MSP119 antibodies were not associated with patent parasitemia. Anti-MSP119 antibody titres correlated positively with age, indicating that development of antibodies to MSP119 may depend on long-term exposure to parasites. Using competitive ELISA, 82% of the samples inhibited the binding of processing-inhibitory monoclonal antibodies (mAb) 12.8 and 12.10 to immobilized recombinant MSP119. The binding of mAb 12.8 in the presence of 18% of these samples .was reduced to less than 10%. This suggest that these samples contain polyc1onal antibodies that have a similar binding specificity to that of mAb 12..S, which recognizes an epitope located in the first epidermal growth factor domain of MSP119. Our data provide useful leads for the design of an MSP119-based vaccine.